The relationship between nutritional status and the eruption of lower permanent incisors in 6-7-year-old students at Candijati 01 elementary school in Arjasa, Jember, Indonesia - Setyorini, Dyah; Berlian Prihatiningrum; Muqsitoh Alfatah, Aysha; Probosari, Niken; Budi Rahardjo, Roedy (International Journal of Dental Research, 2024)
Tooth eruption is a normal movement of tooth to the oral cavity from its growth position in alveolar bone. This process is influenced by various factors, one of which is nutritional status. The aim of this study was to determine the relationship between nutritional status and the eruption of permanent mandibular incisors. This descriptive analytic study with a cross-sectional design involved 43 students aged 6-7 years from Candijati 01 Elementary School, Arjasa, Jember. The nutritional status was assessed using the Body Mass Index (BMI) according to age, The subjects were categorized into three nutritional status groups: underweight, normal, and overweight. Results is analyzed using the Spearman statistical test, indicated a significant relationship between nutritional status and the eruption of permanent mandibular incisors (p<0.05). The conclusion of this study is that there is a significant relationship between nutritional status and the eruption status of perma-nent mandibular incisors in children aged 6-7 years.